Bilateral Combined Discoid Lateral Menisci and Lateral Femoral Condyle Osteochondritis Dissecans Lesions in a Division I Varsity Athlete: A Case Report - Kilcoyne, Kelly G.; Dickens, Jonathan F.; Rue, John-Paul; Keblish, David J. (The Journal of Knee Surgery, 2013)
Discoid menisci can be a source of pain for patients, and pose treatment challenges to the treating surgeon. Additional associated intra-articular pathology, specifically osteochondral defects, can further complicate the clinical picture. The incidence of lateral discoid meniscus is variable based on the population, with a range of 0.4 to 17%, with bilateral involvement in up to 19% of these cases. Osteochondritis dissecans (OCD) is exceedingly rare, with an incidence of 0.015% in one study; however, some authors have suggested a correlation between the development of OCD and the presence of an unstable or torn lateral discoid meniscus. We present a case, the first to our knowledge, of bilateral lateral femoral condyle OCD in the presence of bilateral, asymptomatic, complete lateral discoid menisci.
Keywords: discoid; meniscus; osteochondritis; knee